2008
DOI: 10.1124/dmd.108.021808
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, Distribution, and Excretion of a Next Generation Selective Estrogen Receptor Modulator, Lasofoxifene, in Rats and Monkeys

Abstract: ABSTRACT:Disposition of lasofoxifene (LAS; 6-phenyl-5-[4-(2-pyrrolidin-1-yl-ethoxy)-phenyl]-5,6,7,8-tetrahydro-naphthalen-2-ol. tartrate) was investigated in rats and monkeys after oral administration of a single oral dose of [ 14 C]LAS. Total mean recoveries of the radiocarbon were 96.7 and 94.3% from rats and monkeys, respectively. The major route of excretion in both species was the feces, and based on a separate study in the bile duct-cannulated rat, this likely reflects excretion in bile rather than incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Similarly lasofoxifene creates a very interesting innovation in enhanced pharmacokinetics. Lasofoxifene is extensively metabolized in rats and monkeys with tissues achieving maximal concentrations within one hour of oral administration of 14 C labeled lasofoxifene [53]. There was greater than 95% of lasofoxifene and metabolites excreted in feces through the biliary route with only a small amount of glucoronide.…”
Section: Pharmacokinetics Of Tamoxifen and Raloxifenementioning
confidence: 99%
“…Similarly lasofoxifene creates a very interesting innovation in enhanced pharmacokinetics. Lasofoxifene is extensively metabolized in rats and monkeys with tissues achieving maximal concentrations within one hour of oral administration of 14 C labeled lasofoxifene [53]. There was greater than 95% of lasofoxifene and metabolites excreted in feces through the biliary route with only a small amount of glucoronide.…”
Section: Pharmacokinetics Of Tamoxifen and Raloxifenementioning
confidence: 99%
“… Ion chromatograms of independently characterized glucuronides before and after treatment with aqueous hydroxylamine as described. (a) Mouse urine extract showing the phenolic glucuronides (M3, M4, M7, and M24) of lasofoxifene 23. (b) Ion chromatogram ( m/z 317) of the glucuronide of compound Y.…”
Section: Resultsmentioning
confidence: 99%
“…In the development of lasofoxifene, definitive metabolic studies using radiolabeled drug showed several urinary phenolic glucuronides. 23 Mouse urine from a 14 C-labeled lasofoxifene mass balance study was used to examine the reactivity with hydroxylamine.…”
Section: Lasofoxifene Glucuronidesmentioning
confidence: 99%
“…The extent of absorption of lasofoxifene was investigated in the intact and bile-duct rats after oral administration of single dose of [ 14 C]lasofoxifene [121]. The cumulative excretion amounted to 1.72% in the urine and 95.0% in the feces of intact rats.…”
Section: Absorptionmentioning
confidence: 99%
“…Prakash et al . [121] examined tissue distribution in male and female pigmented rats (Long-Evans) using WBAL following administration of a single oral dose of [ 14 C]lasofoxifene. [ 14 C]Lasofoxifene-related radioactivity distributed rapidly in the rat with most tissues achieving maximal concentrations at 1 h. Tissue exposure was similar in male and female rats, with the greatest exposure in the uvea.…”
Section: Distributionmentioning
confidence: 99%